Physic-chemical aspects of energy substitution technologies in modern production processes of printing enterprises - Shtefan, Yevgenii; Seryogin, Oleksandr (My University, 2024)
Thermodynamic models allow us to evaluate the maximum theoretical efficiency of the process and describe the equilibrium composition of the system. The process of thermochemical conversion is influenced by three macrokinetic restrictions: The restriction associated with the fact that the gasification process tends to the boundary of the formation of free non-gasified carbon. Upon reaching this boundary, an equilibrium is established between the solid and gas phases. The limitation associated with the thermal regime of the process, which, regardless of the reaction parameters determines the efficiency of the process and the composition of the resulting synthesis gas. The restriction associated with the fact that after the onset of a stationary state, additionally added heat to the system is mainly used to heat the reaction products, and not to change their composition.

Термодинамічні моделі дозволяють оцінити максимальну теоретичну ефективність процесу та описати рівноважний склад системи. На процес термохімічного перетворення впливають три макрокінетичних обмеження: Обмеження, пов'язане з тим, що процес газифікації прагне до межі утворення вільного негазифікованого вуглецю. При досягненні цієї межі між твердою і газовою фазами встановлюється рівновага. Обмеження пов'язане з тепловим режимом процесу, який незалежно від параметрів реакції визначає ефективність процесу і склад одержуваного синтез-газу. Обмеження пов'язане з тим, що після настання стаціонарного стану додатково додана теплота в систему використовується в основному для нагрівання продуктів реакції, а не для зміни їх складу.
Keywords: thermochemical conversion; macrokinetic restrictions; gasification process; кафедра електропостачання і енергоменеджменту; термохімічне перетворення; макрокінетичні обмеження; процес газифікації